O Brasil e o multilateralismo comercial: a política externa brasileira em relação à OMC entre 2003 e 2008 - Almeida, Rafael Augusto Ribeiro de (2019)
The goal of this research is to analyze the Brazilian performance in the multilateral trade negotiations, with particular attention to the performance of the Ministry of Foreign Affairs and actors of Brazilian civil society in central instances of the WTO, the Doha Round and the G-20 trade between 2003 and 2008. More specifically, on the one hand, to investigate the intentions and commitments that Brazilian diplomacy has assumed in relation to the other developing countries, in particular G20 members, as well as the role assumed by the country in the Doha Round between 2003 and 2008. On the other hand, it is sought to understand the preferences of Brazilian domestic actors interested or involved in trade negotiations and the space that these actors acquire in the Brazilian foreign policy between 2003 and 2008. The domestic actors delimited in this research were: industrial sector, especially with the National Confederation of Industry (CNI) and with the Brazilian Business Coalition (CEB); the agribusiness sector with the Confederation of Agriculture and Livestock of Brazil (CNA); and social movements with the Brazilian Network for the Integration of Peoples (REBRIP).